Generation of a monoclonal antibody against duck circovirus capsid protein and its potential application for native viral antigen detection - Li, Jinxin; Liu, Fengli; Ren, Zhihao; Fu, Guanghua; Shi, Jizhen; Zhao, Naiyu; Huang, Yu; Su, Jingliang (Frontiers in Microbiology, 2023)
Introduction Duck circovirus (DuCV) infection is currently recognized as an important immunosuppressive disease in commercial duck flocks in China. Specific antibodies against DuCV viral proteins are required to improve diagnostic assays and understand the pathogenesis of DuCV infection. Methods and results To generate DuCV-specific monoclonal antibodies (mAbs), a recombinant DuCV capsid protein without the first 36 N-terminal amino acids was produced in Escherichia coli. Using the recombinant protein as an immunogen, a mAb was developed that reacted specifically with the DuCV capsid protein, expressed in E. coli and baculovirus systems. Using homology modeling and recombinant truncated capsid proteins, the antibody-binding epitope was mapped within the region of 144IDKDGQIV151, which is exposed to solvent in the virion capsid model structure. To assess the applicability of the mAb to probe the native virus antigen, the murine macrophage cell line RAW267.4 was tested for DuCV replicative permissiveness. Immunofluorescence and Western blot analysis revealed that the mAb recognized the virus in infected cells and the viral antigen in tissue samples collected from clinically infected ducks. Discussion This mAb, combined with the in vitro culturing method, would have widespread applications in diagnosing and investigating DuCV pathogenesis.